(untitled) - Schnaars, Steven P. (New York, 1989)
The author identifies the most common mistakes in forecasting technological developments and provides guidelines. He considers forecasts preceding vibrant growth in computers and other major products and provides three key guidelines to reliable, lower-risk forecasting.
Keywords: Technological forecasting,Dự báo công nghệ